The Influence of Christian Religious Education in Family and Parenting Styles on Adolescent Character Formation - Ester, Ester; Rini, Wahju Asjarjo; Triyanto, Yoel; Widiyanto, Mikha Agus; Fernando, Andreas (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
This study aimed to test and prove through data collection that the formation of the character of Christ in adolescents is influenced by the implementation of Christian religious education in the family and parenting patterns. The research method used in this research was the survey method - correlational. Based on the data analysis, the results showed that: 1) Christian religious education in the family had a significant effect on the formation of the character of Christ in adolescents; 2) Parenting patterns have a significant effect on the formation of Christ's character in adolescents; 3) Christian religious education in the family and parenting patterns together have a significant effect on the formation of the character of Christ. Thus, efforts to form the character of Christ in adolescents can be done by increasing the intensity of the implementation of Christian religious education in the family and increasing the right parenting pattern.